(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Arterial hypertension is one of the leading risk factors for cardiovascular disease and premature death in women. Recent studies have shown that this condition is prevalent not only among older women but also among women of reproductive age. In women, the development of arterial hypertension, in addition to traditional risk factors, is closely associated with pregnancy-related hypertensive disorders, gynecological and hormonal changes, psychosocial stress, socioeconomic inequalities, and gender differences in the use of health care services. The aim of this review is to summarize the available scientific evidence on the prevalence, risk factors, clinical consequences, and gender-specific aspects of the management of arterial hypertension in women. Epidemiological studies conducted across different regions indicate significant regional and social disparities in hypertension prevalence, as well as inadequate detection, treatment, and control of the disease, particularly in low- and middle-income countries.